1984
DOI: 10.2307/1939123
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Approach to the Function of Buttresses of Quararibea Asterolepis

Abstract: Buttresses of~owland tropical forest trees have long been thought to serve as structural supports. This morphometnc~l study of the buttresses and other characteristics of Quararibea asterolepzs demonstr~tes and descnbes the nature of the support role played by buttresses. Buttresses tend to grow on the side of the tree that faces the prevailing winds, thereby functioning as tension members that help prevent th_e ~ree from bei~g blown over. The buttresses become proportionately larger as th_e tree grows, prov1d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 14 publications
5
39
0
Order By: Relevance
“…Navez 1930;Richter 1984;Lewis 1988;Ennos 1993). Strong gusts of wind ahead of thunderstorms over Korup are known but not with a consistent wind direction.…”
Section: Buttress Formmentioning
confidence: 99%
See 2 more Smart Citations
“…Navez 1930;Richter 1984;Lewis 1988;Ennos 1993). Strong gusts of wind ahead of thunderstorms over Korup are known but not with a consistent wind direction.…”
Section: Buttress Formmentioning
confidence: 99%
“…If a part of a tree's crown tended to be largely supplied with its mineral nutrients via the lateral buttressed roots directly below it (perhaps an explanation for the interesting observations of Whitford 1906, in this respect), then the pattern in buttressing developed in early life (when the tree was in the sub-canopy with minimal structural requirements) would not necessarily be ideally positioned to supply the tension or compression wood for an asymmetry of the crown on the other side as a large canopy/emergent adult (inferred from Richter 1984). This further explains the complicated and varied patterning in buttress sizes and directions.…”
Section: Buttress Formmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in southwest China shows that the percentage of buttressed trees is highest in the larger diameter classes (He et al 2013). Buttresses are complex features that are regarded as an adaptation to poor tropical soils, enabling trees to form a flat root system in the upper, nutrient richer soil layers while maintaining their mechanical stability and anchorage (Richards 1952, Richter 1984, Ennos 1993, Crook et al 1997, Newbery et al 2009, Niklas 2013. Usually Dipterocarpaceae, Ligumninosae and Sterculiaceae show a greater tendency to produce buttresses than other tree species.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, Swaine (1983) observed that stilt roots may allow individuals to establish at ephemeral sites or sites with high amounts of debris by shifting the rooting location so as to avoid organic debris such as logs. Some studies have also suggested that stilt roots may act as tensioning buttresses and improve anchoring in less-developed substrates or in areas of high wind stress (Henwood 1973, Jeník 1978, Richter 1984. The association of Iriarteoid palms with steep sloped habitats has led to the suggestion that stilt roots may be an adaptation to unstable conditions and provide mechanical stability against uprooting (Henderson 1990, Chiatante et al 2002.…”
mentioning
confidence: 99%